17. REARING OF THE HOUSE DUST MITE DERMATOPHAGOIDES FARINAE IN THE LABORATORY (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the optimal conditions for rearing house dust mites Dermatophagoides farinae in the laboratory. Methods: The study was conducted from July to December 2024 at the National Institute of Malariology, Parasitology, and Entomology. Evaluating the effects of different mite rearing densities on the growth and development of the house dust mite Dermatophagoides farinae. Evaluating the effects of different mite rearing food environments on the growth and development of the house dust mite Dermatophagoides farinae. Results: In the 5 kind of rearing culture environments, the rearing culture environment 5th (includes dried shrimp powder, bread flour, cereal powder in the ratio of 4:7:1 and supplemented with Blomia tropicalis mites in the ratio of 2Dermatophagoides farinae:1Blomia tropicalis) gave the best results for house dust mite growth. The number of house dust mites increased 198.37 times after 8 weeks and 585.5 times after 12. Rearing culture environment 1st (including dried shrimp powder, bread flour, cereal powder in the ratio of 4:7:1) and environment 2nd (including dried shrimp, bread flour, cereal powder, yeast in the ratio of 4:7:1:2) gave the results for house dust mite growth from 93.47-96.23 times after 8 weeks and 237.03-259.35 times after 12 weeks.. The best growth density of house dust mites was at 50 mites/plate with the number of mites increasing 198.37 times and 200.83 times after 8 weeks in the the kind 10g rearing culture environments/plate and 585.50 times and 529.52 times after 12 weeks in the 20g rearing culture environment/ plate. Conclusion: The optimal conditions for house dust mites Dermatophagoides farinae at temperature of 25 - 280C, humidity: 75 - 80%, light: dark time is 14:10 hours with the rearing culture environment including dried shrimp powder, bread flour, cereal powder in the ratio: 4:7:1 and supplemented with Blomia tropicalis mites in the ratio of 2:1 at a house dust mite culture density of 50 mites/10g rearing culture environment/plate.
Keywords: Dermatophagoides farinae; rearing